Drenagem e manejo sustentável de águas pluviais urbanas: O que falta para o Brasil adotar? - Alesi Teixeira Mendes; Gesmar Rosa dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Cities and their populations have suffered from the impacts of accelerated urbanization, with natural disasters, especially involving urban waters. The human and material losses witnessed in recent years, in Brazil and in the world, call attention to the importance of the transition to more resilient and sustainable urban development models. In this way, the objective of this Discussion Paper is to present data and reflect on the trajectory and current conditions in Brazil regarding urban water management. The cut in sustainable rainwater drainage is used as an alternative and trend for the solution to the challenges of rainwater management in the present and future, including due to variations and possible changes in the climate. Using data from the Sistema Nacional de Informaç\~oes sobre Saneamento (SNIS) - a Brazilian National Information System on Sanitation (rainwater drainage, sewage, drinking water, and solid waste) - and the Sistema Integrado de Planejamento e Orçamento (Siop) - a Brazilian Integrated Planning and Budget System - historical and conjunctural elements of urban drainage services in Brazil are discussed. The importance of encouraging the transition of investments to integrate drainage initiatives into the set of urban-housing policies, focusing on efficient and sustainable infrastructures, is highlighted. In this sense, guidelines for public policies are pointed out.
10419/284855
Keywords: H77; O18; Q25; 330; sanitation; sustainable management; urban rainwater drainage; public policies